Review: Potential strength of fly ash-based geopolymer paste with substitution of local waste materials with higherature effect - Subekti, S. (Institute of Physics Publishing, 2017)
This research provided an overview of the potential fly ash based geopolymer paste for application in building construction. Geopolymer paste with various variations of fly ash substitution with local waste material and higherature influence exploited with the fresh and hardened condition. The local waste material which utilized for this study were sandblasting waste, carbide waste, shell powder, bagasse ash, rice husk and bottom ash. The findings of this study indicated that fly-based geopolymer paste with local waste material substitution which had higherature influence ash showed a similar nature of OPC binders potentially used in civil engineering applications. © Published under licence by IOP Publishing Ltd.